Reassessing the Ritz–Einstein debate on the radiation asymmetry in classical electrodynamics. (August 2016) - Frisch, Mathias; Pietsch, Wolfgang
Abstract: We investigate the debate between Walter Ritz and Albert Einstein on the origin and nature of the radiation asymmetry. We argue that Ritz׳s views on the radiation asymmetry were far richer and nuanced than the oft-cited joint letter with Einstein (Ritz & Einstein, 1909 ) suggests, and that Einstein׳s views in 1909 on the asymmetry are far more ambiguous than is commonly recognized. Indeed, there is strong evidence that Einstein ultimately came to agree with Ritz that elementary radiation processes in classical electrodynamics are non-symmetric and fully retarded. Highlights: In-depth analysis of the radiation asymmetry in classical electrodynamics. Re-evaluation of an influential historical debate between Einstein and Ritz. Discussion of Ritz׳s action-at-a-distance approach to electrodynamics. Analysis of the conceptual import of Ritz׳s theory for the radiation asymmetry.